N‐Heterocyclic‐Carbene‐Catalysed Diastereoselective Vinylogous Mukaiyama/Michael Reaction of 2‐(Trimethylsilyloxy)furan and Enones. Issue 12 (15th October 2015) - Wang, Ying; Du, Guang‐Fen; Xing, Fen; Huang, Kuo‐Wei; Dai, Bin; He, Lin
Abstract: N‐heterocyclic carbenes have been utilised as highly efficient nucleophilic organocatalysts to mediate vinylogous Mukaiyama/Michael reactions of 2‐(trimethylsilyloxy)furan with enones to afford γ‐substituted butenolides in 44–99 % yield with 3:1–32:1 diastereoselectivity. Abstract : M and M : N‐heterocyclic carbenes act as highly efficient organocatalysts to mediate the vinylogous Mukaiyama/Michael reaction of 2‐(trimethylsilyloxy)furan and enones to afford γ‐substituted butenolides in 44–99 % yield with 3:1–32:1 anti/syn selectivity.